The nanosized dye adsorbents for water treatment - Homaeigohar, Shahin (Nanomaterials, 2020)
Clean water is a vital element for survival of any living creature and, thus, crucially important to achieve largely and economically for any nation worldwide. However, the astonishingly fast trend of industrialization and population growth and the arisen extensive water pollutions have challenged access to clean water across the world. In this regard, 1.6 million tons of dyes are annually consumed. Thereof, 10%–15% are wasted during use. To decolorize water streams, there is an urgent need for the advanced remediation approaches involving utilization of novel materials and technologies, which are cost and energy efficient. Nanomaterials, with their outstanding physicochemical properties, can potentially resolve the challenge of need to water treatment in a less energy demanding manner. In this review, a variety of the most recent (from 2015 onwards) opportunities arisen from nanomaterials in different dimensionalities, performances, and compositions for water decolorization is introduced and discussed. The state-of-the-art research studies are presented in a classified manner, particularly based on structural dimensionality, to better illustrate the current status of adsorption-based water decolorization using nanomaterials. Considering the introduction of many newly developed nano-adsorbents and their classification based on the dimensionality factor, which has never been employed for this sake in the related literature, a comprehensive review will be presented.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Adsorption; Decolorization; Dye pollution; Nanomaterials; Water treatment